A single-center experience involving the first 50 patients of minimally invasive cardiac surgery of coronary artery bypass grafting: at district level - Parth B. Solanki; Nivedita Vadodaria; Hitendra Kanzaria; Bharat Solanki (Кардиоваскулярная терапия и профилактика)
Aim. To examine the learning curve and results of the first 50 instances of coronary artery bypass grafting (CABG) that were done at our facility using minimally invasive cardiac surgery (MICS).Material and methods. A total of 50 patients received CABG using the left anterior thoracotomy technique between January 2021 and November 2022. We examined the MICS CABG patients' operating hours to assess our learning curve. In addition, we reviewed postoperative outcomes and compared them with those of patients who underwent sternotomy.Results. The median age was 49.5 years (the range was 27-72). Males made up 38 of the group, while females — 12. Ejection fraction (EF) before surgery averaged 40±5%. After exclusion criteria were met, all of these patients underwent CABG by left-sided thoracotomy. The radial artery and saphenous vein were the next alternate conduits, and all patients got left internal mammary artery (LIMA) to left anterior descending (LAD) artery as a conventional transplant. The average incision length was 7.08±0.5 cm. On the pump, only 1 case was completed. Per patient, there were 2.53±0.82 grafts on average. On average, the operation took 130.43±9.78 minutes. The median intensive care unit (ICU) length of stay was 2.82±0.74 days, while the median ventilation time was 5.79±1.80 hours. In our study, there were no conversions and no deaths. After the first 20 cases, we noticed a considerable decrease in operating time, which was our learning curve.Conclusion. Once the learning curve has been overcome, MICS CABG can be performed for multivessel disease with the same comfort for the operator as for a singleor double-vessel disease. Only during the learning curve, and not subsequently, there were greater operating time for MICS CABG observed as a significant difference from the sternotomy technique. While there was no difference in postoperative adverse events, there were notable advantages of MICS vs sternotomy in the parameters of immediate postoperative time such as ventilation time, mean drainage, postoperative discomfort, length of stay in ICU and hospital.